PHF6 interacts with the LMO2 complex in T-cell acute lymphoblastic leukemia - Stanulović, Vesna S.; Binhassan, Sarah; Jaber, Budoor A.; Alazmi, Shimaa; Saleman, Fatma M.B.; Potluri, Sandeep; Pratt, Guy; Ludwig, Christian; Ward, Douglas G.; Hoogenkamp, Maarten (Haematologica (Roma), 2025)
The transcriptional mediator LIM domain only 2 (LMO2) forms a large multi-protein complex together with TAL1/LYL1, HEB/E2A, LDB1 and GATA. This complex regulates transcription from the onset of hematopoietic development and during differentiation. Chromosomal rearrangements involving LMO2 and TAL1 are causative for T-cell lymphoblastic leukemia (TALL). We have identified Plant Homeodomain (PHD)-like Finger 6 (PHF6) as a new LMO2 interacting factor. Somatic mutations in PHF6 have been found to occur in several types of leukemia. We show that PHF6 interacts with LMO2 as a part of the TAL1, GATA2, LDB1 complex in T-ALL and binds to the DNA. These findings show that PHF6 associates with the TAL1/LMO2/LDB1/GATA2 complex and regulates genes that have a major role in blood development, such as SPI1 (PU.1).